Determination of automatic weather station self‐heating originating from accompanying electronics. (13th November 2019) - Pavlasek, P.; Merlone, A.; Sanna, F.; Coppa, G.; Izquierdo, C. G.; Palencar, J.; Duris, S.
Abstract: Atmospheric air temperature values are fundamental in meteorology and climate studies. To achieve high accuracy in the measurements, the features, characteristics and performances of instruments are of high importance. This study focuses on the most commonly used temperature sensors within automatic weather stations, with a specific focus on evaluating the self‐heating effect. Self‐heating in automatic weather stations originates not only from the temperature sensor itself but also from the electrical components housed together within. This effect introduces extra heating in the system, causing biases and errors in temperature records. The conducted measurements show the temperature change in the close vicinity of the thermometers over a time period of more than 66 hr with electric current and voltage supply values recommended by the respective sensor manufacturers. Furthermore, the temperature changes after increasing the voltage supply levels up to 80% of the maximum voltage recommended by the manufacturer are presented as well. The results of overall self‐heating indicated a +0.07°C increase in temperature for the tested sensors when using the manufacturers' recommended electric current and voltage supply. However, the use of elevated voltage levels shows a considerably higher temperature increase in the vicinity of the temperature sensors. In the present study, the measured difference from the initial measured temperature can be as high as +0.32°C. Abstract : This study focuses on the most commonly used temperature sensors within automatic weather stations, with a specific focus on evaluating the self‐heating effect, which originates not only from the temperature sensor itself but also from the electrical components housed together within. The results of overall self‐heating indicated a 0.07°C increase in temperature for the tested sensors when using the manufacturers' minimum recommended electric current supply. The use of elevated voltage levels up to 80% of recommended values shows a temperature increase as high as 0.32°C.